THE SPIRITUALITY IN THE HOSPITAL CONTEXT: : A PSYCHOLOGICAL LOOK - Gomes de Oliveira Neto, Jorge (Health and Society, 2021)
This article aims to review studies on spirituality and health psychology. The need to discuss this topic arose from the fact that there is some difficulty on the part of psychologists in dealing with the spiritual dimension of their patients. Due to the possibility of accessing the experiences of authors who have already researched on the subject, its technical procedure took place through bibliographical research. As a theoretical foundation, authors who discuss spirituality and health, especially in the hospital context, were used. According to the theoretical bases found, it was possible to verify that there are still difficulties in understanding and considering the spiritual dimension as part of the human being in a holistic perspective. In this sense, such difficulty is consequently reflected in the hospital environment. This conclusion becomes relevant in order to encourage researchers and psychologists to discuss and research more frequently on the developed theme, and thus enable patients to have a better hospitalization process.